UPAYA UNITED NATIONS WOMEN (UN WOMEN) DALAM MEWUJUDKAN KESETARAAN GENDER MELALUI KAMPANYE HEFORSHE DI INDONESIA TAHUN 2016-2019 - Anissa, Rahmah Nurul; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to find out how the efforts of the UN Women International Organization through the HeForShe Campaign in realizing gender equality through the HeForShe campaign in Indonesia in 2016-2019. The issue of gender equality in Indonesia is still an issue that is still being discussed at this time. For this reason, UN Women and the Government of Indonesia cooperate in dealing with the issue of gender equality caused by the patriarchal culture and the negative stigma of society towards women. This study uses the theory of the role of International Organizations, Feminism perspective and level of group analysis. Literature research method, which utilizes secondary data obtained through library research obtained from various literatures such as books, journals, e-mail, newspapers, annual reports of several relevant agencies, documents, or valid websites. The results of this study indicate that the efforts made by UN Women through the HeForShe campaign create a Three ends program, Safe cities, increase women's awareness (public awareness), and increase women's participation in politics also create a work environment that is safe from discrimination.Keywords: Indonesia, HeForShe Campaign, Gender Equality, UN Women.